A comparative study of population traits between two South American populations of the striped-legged hermit crab Clibanarius vittatus - Mantelatto, Fernando Luis; Fernandes-Goes, Lissandra Correa; Fantucci, Marina Zilio; Biagi, Renata [UNESP]; Miguel Pardo, Luis; de Goes, Joao Marcos (Gauthier-villars/editions Elsevier, 2010)
The striped-legged hermit Crab Clibanarius vittatus, with a geographical distribution covering a wide range of latitudes in the western Atlantic, was selected for a comparative study on population features between two different areas of the Brazilian coast that are separated by approximately 3000 km. The two populations Were sampled concurrently for nine months. The populations in northern and southeastern Brazil showed different profiles in terms of size of specimens, sex ratio, and shell occupation. The observed plasticity of these life-cycle traits of C. vittatus in relation to local environmental conditions is discussed. (C) 2009 Elsevier Masson SAS. All rights reserved
Keywords: Anomura; Brazil; Cline; Diogenidae; Distribution